Outcomes of Colorado children with acute flaccid myelitis at 1 year - Martin, Jan A. (Neurology, 2017)
OBJECTIVE: We describe long-term functional, neurodiagnostic, and psychosocial outcomes of a cohort of 12 children from Colorado diagnosed with acute flaccid myelitis (AFM) in 2014. METHODS: Children were assessed every 3 months for 1 year or until clinical resolution. Assessments included neurologic examination, MRI, EMG/nerve conduction studies (NCS), functional measures (Assisting Hand Assessment, Hammersmith Functional Motor Scale), and Patient-Reported Outcomes Measurement Information System questionnaires. RESULTS: Eight of 12 children completed the study. Six of 8 had persistent motor deficits at 1 year; 2 demonstrated full recovery. Four were not enrolled, 2 of whom reported full recovery. The 6 affected were weakest in proximal muscles, showing minimal to no improvement and significant atrophy at 1 year. All patients improved in distal muscle groups. Cranial nerve dysfunction resolved in 2 of 5 and improved in all. Four of 5 showed progressive functional improvement at 6 and 12 months. Two of 8 reported pain at 1 year. Three of 8 reported depressive symptoms. Repeat MRI was performed in 7 of 8 children a median of 7 months after onset and showed significant improvement or normalization in all but one child. Repeat EMG/NCS was performed on 4 children a median of 8 months after onset and showed ongoing denervation and chronic reinnervation in 3 children with persistent deficits. CONCLUSIONS: At 1 year, children with AFM demonstrated functional gains but weakness persisted. EMG changes correlated with persistent deficits better than imaging. Despite improvements, AFM had substantial long-term functional effects on affected children.